THE IMPORTANCE OF CULTIVATING BUCKWHEAT AS UNIQUE AND ENVIRONMENTALLY ORIENTED CROP - Tryhub, O. V.; Kutsenko, O. M.; Liashenko, V. V.; Nohin, V. V. (Scientific Progress & Innovations, 2022)
The prospects of cultivating buckwheat as environmentally oriented crop, which owing to its biological properties and economic characteristics, can ensure the profitability of production and improve its ecological environment, was proven in the article. Owing to buckwheat’s unique properties, it is valuable as a preceding and soil improving crop and is grown using pesticide-free technology; it is a honey-bearing and raw material crop. Buckwheat grain is a source of biologically active substances, vitamins, minerals, and others as well as the products of its processing for manufacturing functional products having curative and useful properties. Buckwheat is also valuable because of loss free technology of its cultivation and versatile use. It has been determined that buckwheat is a fallow and good preceding crop for winter crops; it positively affects the soil: the field stays weed free and fluffy. Buckwheat can fix nitrogen in the root rhizosphere non-symbiotically with Azospirillum bacter bacteria, etc. It was analyzed as a green manure crop, which assists in fertilizing soil with a whole complex of essential macro- and micro-elements. Buckwheat resistance to pests and diseases was registered, which together with pesticide-free cultivation technology, minimizes the use of chemical means of protection. The place of buckwheat as one of the best honey-bearing crops in the development of apiculture in Ukraine was determined. The prospects for creating functional products having curative and useful properties for humans besides being a food crop, was substantiated. It has been mentioned that the priority of cultivating buckwheat is also stipulated by the loss free technology of its production and versatile use in the pharmaceutical industry and folk medicine, livestock and poultry farming, and mushroom growing, etc.